Building CancerCommunity.sg, a local cancer web portal. - Koh, Sabrina Xin Fei. (2012)
This report describes the process of building CancerCommunity.sg, a one-stop local web portal for the local cancer community. It begins with a rationale and description of the entire project, providing findings of background research done on the topic. Thereafter, it describes the information-gathering process from local cancer stakeholders in order to make the web portal relevant to the local cancer community. The following section then provides a detailed analysis of how each feature of the web portal was decided on, based on the inputs of various stakeholders. Management protocol for the sustainability of the web portal is also included, and the report concludes with a final segment that addresses possible future developments of the web portal.